FUNGSI KONTROL DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) TERHADAP PENDIDIKAN GRATIS DI KABUPATEN HALMAHERA SELATAN - Sukur Suleman (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
This study discusses the oversight function of the Regional House of Representatives in the implementation of free education as well as the factors that influence the DPRD in the implementation of its supervisory function towards the implementation of free education in South Halmahera Regency. The review of this research is descriptive qualitative, that is, the research provides a clear and complicated picture of what is examined and becomes the subject of discussion, data obtained from informants through observation, interviews and document analysis. The results showed how the supervision of the Regional People's Representative Council in the implementation of free education in South Halmahera Regency was not optimal because the DPRD was more preoccupied with personal affairs and political parties, then the supervisory function was also needed by the ability of DPRD members, political competition and DPRD protection.